2004
DOI: 10.1007/s00285-003-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations and patterns in spatially discrete models for developmental intercellular signalling

Abstract: Abstract. We extend previous models for nearest neighbour ligand-receptor binding to include both lateral induction and inhibition of ligand and receptor production, and different geometries (strings of cells and hexagonal arrays, in addition to square arrays). We demonstrate the possibility of lateral inhibition giving patterns with a characteristic length scale of many cell diameters, when receptor production is included. In contrast, lateral induction combined with inhibition of receptor synthesis cannot gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 40 publications
4
68
0
Order By: Relevance
“…While the period-two pattern is distinguished by its dominance, the consideration of other patterning modes is nonetheless significant in related cell-signalling studies; for instance, in arrays of hexagonal cells, the fine-grained patterning regime corresponds to patterns containing three cells rather than two. In addition, microscopic patterns of considerably longer wavelength can be observed in developing tissues and Webb & Owen (2004b) have shown that such patterns may be generated in related models of lateral inhibition. Multiscale analyses of such considerations will be presented elsewhere.…”
Section: Patterning and Stability -Bifurcation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…While the period-two pattern is distinguished by its dominance, the consideration of other patterning modes is nonetheless significant in related cell-signalling studies; for instance, in arrays of hexagonal cells, the fine-grained patterning regime corresponds to patterns containing three cells rather than two. In addition, microscopic patterns of considerably longer wavelength can be observed in developing tissues and Webb & Owen (2004b) have shown that such patterns may be generated in related models of lateral inhibition. Multiscale analyses of such considerations will be presented elsewhere.…”
Section: Patterning and Stability -Bifurcation Analysismentioning
confidence: 99%
“…The positive parameters k, h, a and b determine the feedback strength. The value of the exponent k expresses whether Delta-Notch binding is monovalent (k = 1) or cooperative (k 2); examples of such binding phenomena are given in Webb & Owen (2004b). We note that, In vivo, Delta-Notch binding and the resulting Delta production will be dependent on the cell's biochemical and biophysical environment.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical biologists and mathematicians have successfully modeled the Delta-Notch signaling process by sets of coupled ordinary differential equations (ODEs) [5,13,15,23]. We consider the simple model in [5], where for the i th cell, ni denotes the levels of Notch activity, and di denotes the levels of Delta activity.…”
Section: Inter-cell Biological Modelsmentioning
confidence: 99%
“…Lateral induction (positive feedback between ligandreceptor binding and subsequent ligand production) was accommodated and the range over which juxtacrine signals may be transmitted was studied; Wearing and Sherratt (2001) performed a comprehensive nonlinear analysis of this model, highlighting that linear analysis alone is unable to predict the model's behaviour for large numbers of cells. Webb and Owen (2004) extended this model, considering the dynamics of ligand and free and bound receptors in systems of varying geometry (strings and square or hexagonal arrays), showing that lateral inhibition can produce patterns with a lengthscale of many cell diameters and that cell shape is a crucial determining factor in the patterns produced.…”
Section: Introductionmentioning
confidence: 99%